MICRO-HISTÓRIAS NO JUDICIÁRIO - José Renato Nalini (TRF2, 2020)
In the records, the stories, the events and their main characters have always been in evidence, however, on several occasions, subject to the extraordinary, they are locked up in their anonymity, never achieving the due recognition they deserve. In the course of life, many people go through and modify the reality of an individual, whether intentionally or not, however, these forgetfulness is common. Analyzing his history, he recalls moments of the author and micro-stories of those who accompanied him and intervened in his life, in short, his professional trajectory, going through remarkable events that led him to be who he is. In this brief autobiographical account, we intend to break down particles from a trajectory in the Justice system, in obedience to the historiographic method and, more particularly, to its aspect called microhistory. As a result, we hope to present a practical and concrete example of this peculiar form of narrative to the specialized community.